Transforming Elementary Science Education Through Generative AI-Augmented Stem Learning on Renewable Energy - Arip Nurahman; Irma Fitria; Surya Gumilar; Ali Ismail; Rizal Adimayuda; Dini Andriani (Pendikdas: Pendidikan Dasar, 2026)
The integration of renewable energy education into elementary science learning is essential for developing students’ sustainability awareness and scientific literacy from an early age. This study explores the implementation of Generative Artificial Intelligence (GenAI) augmented STEM learning on solar cell technologies in elementary science education. The research aims to investigate how AI-supported STEM activities can improve students’ understanding of renewable energy concepts, engagement in science learning, and environmental awareness. Using a design-based research approach, elementary students participated in project-based science activities involving simple solar cell experiments and renewable energy exploration. Generative AI tools were utilized to assist students in visualizing scientific concepts, generating ideas, supporting inquiry-based discussions, and enhancing problem-solving processes during classroom learning. The learning framework integrated STEM education principles with renewable energy content and sustainability-oriented science learning. The findings indicate that GenAI-augmented STEM learning positively supports students’ conceptual understanding of solar energy, creativity, collaborative learning, and motivation in elementary science classrooms. The study also highlights the potential of Generative AI as an innovative educational tool for promoting future-oriented and sustainability-focused science education in primary schools.